Lung ultrasound in children and adolescents with long-term effects of COVID-19: Initial results - Gräger, Stephanie; Pfirschke, Rosalie; Lorenz, Michael; Vilser, Daniel; Krämer, Martin; Mentzel, Hans-Joachim; Glutig, Katja (Frontiers in Pediatrics, 2023)
Chronic health effects following acute COVID-19 are increasingly observed as the pandemic continues and are grouped under long COVID. Although the acute course of the COVID disease is often milder, long COVID also affects children and adolescents. Because the symptoms are often unspecific both their origin and suitable diagnostics are still unclear. Therefore, in this prospective observational study we examined 30 children with long COVID by lung ultrasound and compared the results with those of 15 lung-healthy children. In our study, no significant difference was found between the two groups in the morphologic criteria of lung ultrasound on the pleura or pleural lung structures. Our finding is congruent with the current, albeit sparse, data. It is possible that the causes of the persistent thoracic symptoms in long COVID might be more likely to be presented in functional examinations, but not morphologically imageable. Further investigations on morphological and functional changes in long COVID Patient is needed.